2023
DOI: 10.1029/2022wr032719
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Variations From Boreal Forests to the Tundra

Abstract: Soil moisture has a profound influence on life on Earth, and this vital water resource varies across space and time. Here, we explored soil moisture variations in boreal forest and tundra environments, where comprehensive soil moisture datasets are scarce. We installed soil moisture sensors up to 14 cm depth at 503 measurement sites within seven study areas across northern Europe. We recorded 6,138,528 measurements to capture soil moisture variations of the snowless season from April to September 2020. We desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…In general, the cross-validation statistics indicated that the models performed well, but also that there was large variability across the response variables ( Table 3 ). On average, the cross-validated R 2 value was 0.61 (median 0.64), which can be considered good when compared to previous studies in high-latitude regions with relatively similar study settings (Aalto et al, 2022; Greiser et al, 2018; Kemppinen et al, 2023). The best performing models had response variables which described summer and early autumn conditions.The worst-performing models were related to the freeze-thaw frequency in the soil and to temporal variability in soil moisture.…”
Section: Technical Validationsupporting
confidence: 57%
See 2 more Smart Citations
“…In general, the cross-validation statistics indicated that the models performed well, but also that there was large variability across the response variables ( Table 3 ). On average, the cross-validated R 2 value was 0.61 (median 0.64), which can be considered good when compared to previous studies in high-latitude regions with relatively similar study settings (Aalto et al, 2022; Greiser et al, 2018; Kemppinen et al, 2023). The best performing models had response variables which described summer and early autumn conditions.The worst-performing models were related to the freeze-thaw frequency in the soil and to temporal variability in soil moisture.…”
Section: Technical Validationsupporting
confidence: 57%
“…All logger data were quality-filtered and preprocessed (see detailed descriptions of the data cleaning methods in Aalto et al 2022 andKemppinen et al 2023). In summary, 1) we removed all data outside the period during which the logger was in field; 2) we removed all unrealistically high or low temperatures and moisture values; 3) we cross-correlated the time series across loggers aiming to identify unrealistically high sudden peaks (or reversed drops) in the data and removed them; 4) we plotted all individual time series, one site and month at the time, and checked visually whether there were any clearly erroneous data and removed them; 5) if there were data for a logger from a time when the logger was under stable 'office' conditions outside of the field, we used that data to check and correct for potential systematic differences across the three temperature sensors within the logger.…”
Section: Microclimatic Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have important local ecosystem impacts. Spatio‐temporal variations of soil moisture are an important driver of greenhouse gas fluxes (Lohila et al, 2016; Virkkala, 2020) as well as fine‐scale patterns of vegetation properties (Kemppinen, 2020; le Roux et al, 2013). Therefore, through various feedback mechanisms, soil moisture in the tundra plays an important role in global change and its accurate predictions are fundamental to our ability to understand tundra ecosystems now and in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Local‐scale experimental warming was found to increase decomposition (Björnsdóttir et al 2021), yet microclimate and topography were not found to explain the variation decomposition in a tundra landscape in Western Greenland (von Oppen et al 2022), highlighting remaining questions about the controls of tundra litter decomposition across scales. Tundra ecosystems exhibit heterogeneity in both in vegetation patterning and in local environmental conditions – for example, unique topographical and soil conditions driven by permafrost dynamics and seasonal snowmelt dynamics (Elmendorf et al 2012a, b2012a, Myers‐Smith et al 2015, Davidson et al 2016, Ackerman et al 2017, Bjorkman et al 2018, Kemppinen et al 2023). Therefore, we may expect to see variance in decomposition explained by regional macroclimate, and some explained by local‐scale conditions.…”
Section: Introductionmentioning
confidence: 99%